Influence of carbon nanostructures in photoelectrocatalytic water-splitting of ZnO photoanodes / Teh Swe Jyan - Teh, Swe Jyan (2017)
Photoelectrocatalytic (PEC) water-splitting is an active field of research as a sustainable technology utilising solar energy to produce hydrogen, H2 fuel from water. The application of nanostructured carbon materials e.g. reduced graphene oxide (rGO) as promoters for PEC water-splitting photoelectrodes offers many advantages such as cost-effectiveness, chemical stability and tunable properties. Nanostructured carbons obtained from the hydrothermal carbonisation (HTC) of renewable carbon precursors (HTC-biocarbon) shows interesting catalytic activity but its poor electroconductivity limits its application in PEC water-splitting; thus, efforts to increase the sp2 content and diffusion distance may enhance its potential application as promoter for PEC water-splitting. As such, the present thesis sought to investigate the optimal conditions for preparing electrochemically reduced GO (rGO) for the synthesis of rGO-hybridised ZnO photoanodes. Also, HTC-biocarbons were produced using ZnCl2/NaCl and polyvinyl alcohol (PVA) in the hydrothermal carbonisation of renewable carbon precursors for the purpose of modifying the sp2 content and morphology of the HTC-biocarbon product, respectively. The Ph.D. project was carried out to achieve the following objectives: (1) To identify the potential of HTC-biocarbon materials prepared through modified HTC synthesis method as carbon-based promoter for PEC water-splitting photoanodes and (2) To identify optimum preparation methods to obtain higher photoelectric performances in carbon-supported ZnO photoanodes. The effect of modifying the HTC process with ZnCl2/NaCl activating agent and PVA soft template on the sp2 content and morphology of the HTC-biocarbon was investigated. In this study, a porous HTC-biocarbon with surface area up to 597.6 m2 g-1 was prepared using ZnCl2/NaCl as activating agent in the HTC of oil palm shell fibre. An increase in sp2 content was observed with increasing temperature and in the presence of activating agent. The application of PVA as soft template changed the morphology of the HTC-biocarbon product to form a hybrid carbon-carbon structure, consisting of graphene-like sheets and carbonaceous microspheres. rGO-hybridised ZnO thin films were prepared using electrochemical reduction of GO and electrodeposition to deposit the rGO and ZnO layers, respectively. The thin films were prepared in two configurations i.e. (1) ZnO grown on rGO (rGO/ZnO) and (2) rGO coated on ZnO (ZnO/rGO), in order to investigate the effect of layer ordering on the Applied Bias Photon-to-Current Efficiency (ABPE). The rGO/ZnO sample demonstrated the highest ABPE of 0.89 %, due to enhanced electron transfer at the collector-semiconductor interface. The effect of GO electrochemical reduction method was further investigated for rGO/ZnO thin films. It was found that rGO prepared under high flux and rate-controlled conditions during the electrochemical reduction of GO resulted in optimum photo-conversion efficiency in rGO/ZnO films. The highest photocurrent density was observed for rGO/ZnO prepared using CV(1,1) and CV(10,50) ERGO films, at 0.73 and 0.69 mA cm-2 respectively. The onset potential of ZnO was reduced from -0.46 to -0.56 V vs Ag/AgCl for the rGO/ZnO film prepared using CV(10,50), which suggested that rGO/ZnO film prepared using CV(10,50) ERGO film provided the lowest overpotential for the oxygen evolution reaction (OER). The scan rate, number of scan cycles, duration and applied potential are important parameters which allow control between diffusion- and rate-controlled reactions.